Diversity of Legumes in the Cashew Agroforestry System in East Timor (Southeast Asia) - Guterres, Lara (2022)
Cashew is an important export-oriented crop in several tropical countries, often under monocropping systems. Intercropping with legume species is promoted as a sustainable practice, enhancing agricultural productivity and providing nutritional food sources to rural communities. This study aimed to characterize the diversity of Leguminosae (or Fabaceae) in the cashew agroforestry systems of East Timor (Southeast Asia). Fourteen cashew orchards were sampled across the country, and information about leguminous species uses was collected from local populations. About 50 species are commonly part of the country’s cashew agroforestry system, many of them simultaneously used as food, fodder, and in traditional medicine. Six bean species—Cajanus cajan (L.) Huth, Phaseolus lunatus L., Phaseolus vulgaris L., Vigna angularis (Willd.) Ohwi and H.Ohashi, Vigna radiata (L.) R.Wilczek and Vigna unguiculata (L.)Walp.—are largely used as food. The mineral contents of these beans revealed relevant differences between species and, in some cases, between types (seed colour) within species. Periods of hunger and low food variety are frequent in East Timor, reflecting a very poor nutritional state of the population. Knowing and using legumes for local nutrition, as well as for healthcare and well-being, adds great value to these species as components of East Timor cashew agroforestry systems